Transalkylation of alkyl aryl sulfides with alkylating agents. Issue 5 (1st February 2018) - Nawrot, Daria; Kolenič, Marek; Kuneš, Jiří; Kostelansky, Filip; Miletin, Miroslav; Novakova, Veronika; Zimcik, Petr
Abstract: The reaction of methyl iodide with tert -butylphenylsulfide in DMF leads to a transalkylation that produces methylphenylsulfide. This transalkylation reaction was further studied by 1 H NMR spectroscopy. The polarity of the solvent, the electron density on the sulfur atom, and the strength of the alkylating agent (MeI, EtI, BuI, dimethyl sulfate, or dimethyl carbonate) played important roles in the reaction. The suggested mechanism of the reaction involves the formation of a dialkyl aryl sulfonium salt that subsequently eliminates the radical. This mechanism was supported by the observation of higher conversion rates for compounds with more branched alkyl groups on the sulfur atom, which may lead to the formation of more stable radicals. Graphical abstract: Highlights: Alkyl aryl sulfides are transalkylated using various alkylating agents. Reaction depends on polarity of the solvent and electron density on the sulfur. Suggested mechanism involves formation of sulfonium salts as intermediate.